Diversidad polínica en el bosque siempre verde piemontano de la cordillera occidental de Los Andes en la comunidad de Malki – hacienda Machay en el período 2021 – 2022. - Mañay Chimborazo, Alba Liliana (2022)
The purpose of this research study was to carry out a floristic inventory of the tree and shrub species, as well as the morphological description of the pollen grain of the shrub species collected in the ‘Machay’ farm at the altitudinal level of 300 to 1400 meters above sea level. A 50 m x 50 m plot was drawn up at this site, where a floristic inventory of the species was made, taking into account only the trees that had a diameter at breast height (DBH) greater than or equal to 30 cm, these individuals were registered and collected for the cabinet phase. Pollen samples were collected by trail and road considering the height of the corresponding level. The main purpose of this study is to know the species found in the study area and also to know the morphology of pollen to make a photographic catalog. In the plot plotted 77 were recorded, of which only 71 tree species were found to be taxonomically classified, belonging to 9 families, where it was evidenced that the EUPHORBIACEAE family has the largest number of individuals with 25%, where respectively the one with the highest relative dominance is the ARECACEAE family with 22.13%. The study site has a high Simpson's diversity index of 0.85. The morphological classification of the pollen grain, M1 was identified as small size with 17.9 µm, M2 as large size with 53.7 µm, M3 as large size with 269 µm and M4 as medium size with 26.9 µm, with spheroidal and ellipsoidal shapes. In the taxonomic classification, 3 different families were identified BIGNONIACEAE, BROMELIACEAE, and MALVACEAE. This study contributes to the conservation, preservation, and management, through the research the value of the use of each of the families was determined, whether for housing, wildlife feeding, carbon storage, protection of water sources, climate regulation, capable of absorbing heavy materials improving soil fertility and pollination, based on this diagnosis the owners of the farm can carry out programs or projects for supportable and sustainable management of natural resources, to maintain the balance.